Formulation Of A High-Fidelity Nuclear Fission Sites Convergence Detection Method In Monte Carlo Reactor Safety Assessments - Chin, Ken Fui (2023)
Monte Carlo (MC) neutron transport simulation is a widely used computational tool for assessing the safety of various nuclear technologies, including nuclear reactors. During the simulation, an initial guess of the neutron source distribution is required, and as several MC cycles are simulated, it converges to the true distribution. The outcomes from the initial cycles are discarded, and the outcomes from the subsequent cycles are accumulated to obtain a statistically meaningful result. Therefore, accurately identifying the convergence trend is crucial to prevent error accumulation from the initial guess. Traditional convergence diagnostic techniques rely on discretizing the problem geometry, and the selected meshing scheme heavily influences their performance and accuracy. This research formulated and refined a novel mesh-free convergence diagnostic indicator called Fourier fundamental mode coefficient (FFMC).